Contemporary theatre in education - Wooster, Roger (Intellect, 2007)
Theatre in Education emerged in the mid-sixties as a unique hybrid of performance and child-centred learning. Contemporary Theatre in Education charts the creation and adaptation of this 'hybrid' through the changing political, economic and educational environment. It also takes a 'snapshot' of the TIE being created today, considering all the projects being performed in Wales during a single month. The projects are analysed and every TIE director interviewed about the work and the policies of their companies. It becomes very clear that that the distinction between TIE and Children?s Theatre is.